2020
DOI: 10.3390/su12052068
|View full text |Cite
|
Sign up to set email alerts
|

Developing Sustainable Decision Performance for Science and Technology Industries in China

Abstract: This study considers the mediating role of top management teams' (TMTs) behavioral integration in exploring the relationship between the strategic decision-making process (SDMP; procedural rationality and constructive political behavior) and sustainable decision performance (decision quality and decision satisfaction). Survey data totaling 580 from the TMTs of the science and technology enterprises from first-tier cities in China were analyzed through structural equation modeling. The results indicate a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Papadakis et al (1998) found that evidence of a positive relationship between corporate performance and comprehensiveness/rationality. Similarly, others have argued that more rational decisions may themselves lead to better performance (Smith et al, 1988;Lin et al, 2019;Meng et al, 2020). Because top managers make strategic decisions through a rational process and gathering necessary information, we expect that this kind of decision-making process will result in higher-quality decisions, which result in better performance:…”
Section: Strategic Decision-making Style and Performancementioning
confidence: 90%
See 1 more Smart Citation
“…Papadakis et al (1998) found that evidence of a positive relationship between corporate performance and comprehensiveness/rationality. Similarly, others have argued that more rational decisions may themselves lead to better performance (Smith et al, 1988;Lin et al, 2019;Meng et al, 2020). Because top managers make strategic decisions through a rational process and gathering necessary information, we expect that this kind of decision-making process will result in higher-quality decisions, which result in better performance:…”
Section: Strategic Decision-making Style and Performancementioning
confidence: 90%
“…Furthermore, our results show that experienced TMTs tend to make strategic decisions more slowly, while transformational leaders tend to speed up decision-making. It is important to know that both the demographic and psychological characteristics of top managers may influence decision-making styles (Gu et al, 2016;Meng et al, 2020), which, in turn, may affect firm performance. These findings can be applied to strategic human resource management to build competitive advantages, including recruitment, selection and training.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The TMT's behavioral dynamics provide a more complete perception of organizational performance than an individual executive's actions. Social interactions among team members have an impact on behavioral integration (BI), a joint effort [53,54]. Therefore, BI becomes embedded within the relational network, promoting collaboration within the TMT, known as top management team behavioral integration (TBI) [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%